Assessment of Radiation Protection Practices in Diagnostic Radiology Facilities in Pekanbaru, Indonesia - Mohammad Yoshandi; Annisa (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: The use of ionizing radiation in diagnostic radiology carries the potential for adverse health effects. Therefore, adherence to radiation protection practices is essential to ensure the safety of both patients and staff. This study aimed to evaluate radiation protection practices in diagnostic radiology facilities in Pekanbaru, Indonesia. Methods: A cross-sectional study was conducted in all diagnostic radiology facilities in Pekanbaru. Data were collected using a structured questionnaire, observation checklists, and measurements of radiation dose levels. The questionnaire assessed the knowledge, attitudes, and practices of radiation workers regarding radiation protection. Observation checklists were used to evaluate the availability and use of personal protective equipment, radiation warning signs, and shielding. Radiation dose levels were measured using thermoluminescent dosimeters. Results: A total of 30 diagnostic radiology facilities participated in the study. The majority of radiation workers (80%) had received formal training in radiation protection. However, only 60% of facilities had a written radiation protection program. Personal protective equipment was available in all facilities, but its use was not always consistent. Radiation warning signs were present in most facilities, but their placement was not always optimal. Shielding was adequate in most facilities, but some areas required improvement. Radiation dose levels were within permissible limits in all facilities. Conclusion: Radiation protection practices in diagnostic radiology facilities in Pekanbaru are generally good. However, there is room for improvement in some areas, such as the development and implementation of written radiation protection programs, consistent use of personal protective equipment, and optimization of radiation warning signs and shielding.